2021
DOI: 10.1071/fp20104
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the photosynthesis performance in japonica rice during natural leaf senescence using OJIP fluorescence transient analysis

Abstract: Rice undergoes leaf senescence accompanied with grain filling when the plants reach the end of their temporal niche, and a delay in leaf senescence ultimately improves the yield and quality of grain. To estimate the decline in photosynthesis during leaf senescence and to find an efficient and useful tool to identify rice genotypes with a longer duration of active photosynthesis, we examined PSII photosynthetic activity in the flag leaves of japonica rice Shennong265 (SN265) and Beigeng3 (BG3) during leaf senes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…This fast tool, based on non-invasive intact measurements, is advantageous in that it reveals multiple components of PSII function with a higher resolution of time-dependent dynamic responses to heat impact during drought stress. OJIP kinetics have been adopted for screening different varieties of crops subjected to heat or drought stress [ 18 , 23 , 24 , 25 , 26 , 27 , 28 ], and for tracing the senescence of rice [ 29 ] and some European oak tree species [ 19 ]. The technique links the different phases of the rise of the fluorescence signal with the redox states of multiple components of photosystem II (PSII) [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…This fast tool, based on non-invasive intact measurements, is advantageous in that it reveals multiple components of PSII function with a higher resolution of time-dependent dynamic responses to heat impact during drought stress. OJIP kinetics have been adopted for screening different varieties of crops subjected to heat or drought stress [ 18 , 23 , 24 , 25 , 26 , 27 , 28 ], and for tracing the senescence of rice [ 29 ] and some European oak tree species [ 19 ]. The technique links the different phases of the rise of the fluorescence signal with the redox states of multiple components of photosystem II (PSII) [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that compared with ZH11, the contents of CAT, POD, and SOD in IL decreased by 46.49, 8.45, and 56.15%, respectively ( Figure 6 B). Notably, the difference in peroxidase content will inevitably lead to a difference in ROS content [ 37 , 38 ]. As expected, compared with ZH11, the content of H 2 O 2 in IL was significantly reduced by 10.55%, but the production rate of O 2 − was significantly increased by 8.39 times ( Figure 6 C,D).…”
Section: Resultsmentioning
confidence: 99%
“…Low temperature is one of the common abiotic stresses in uences on plant growth, development and yield [46][47][48] . At the late stage of corn powder, the occurrence of low temperature will induce the generation of free radicals in plants, lead to bio lm phase transformation and change the degree of green retention of leaves 49,50 . In the later stage of pollination, higher chlorophyll content in leaves can maintain vigorous through photosynthesis, which is particularly important for improving crop quality and yield 51,52 .…”
Section: Discussionmentioning
confidence: 99%